Yolo, a robot for creativity: A co-design study with children - Paiva, A.; Paiva, A.; Paiva, A.; Paiva, A.; Arriaga, P.; Guy Hoffman (16th International ACM Conference on Interaction Design and Children, IDC 2017, 2017)
This paper describes the design and development of Yolo, a social robot aimed at boosting creativity in children. Creativity is one of the most sought-after competencies as we move from industrialized economies, in which standardized knowledge was imperative, to creative economies, where the ability to innovate is crucial for the workforce. \yolo is a robot to be used by children as a tool to boost new ideas and stimulate their creativity. This paper describes how established educational strategies that enhance creativity were combined with co-designing with children as informants to reach the the prototype design of the robot.